Laminar burning velocities of CH4/O2/N2 and oxygen-enriched CH4/O2/CO2 flames at elevated pressures measured using the heat flux method. (1st January 2020) - Wang, Shixing; Wang, Zhihua; He, Yong; Han, Xinlu; Sun, Zhiwei; Zhu, Yanqun; Costa, Mario
Highlights: The laminar burning velocities of CH4 /O2 /N2 (CO2 ) flames were measured up to 0.5 MPa. Numerical simulation results showed mixed agreement with experimental data. The thermal-diffusion and chemical effects of CO2 dilution were quantified. The pressure dependence of laminar burning velocity showed non-monotonic behavior. Abstract: Laminar burning velocities ( S L ) of CH4 /O2 /N2 and oxygen-enriched CH4 /O2 /CO2 flames were measured at elevated pressures up to 0.5 MPa and equivalence ratios ranging from 0.6 to 1.6. The oxygen molar fraction was varied from 0.18 to 0.23 in the O2 /N2 mixtures and from 0.31 to 0.42 in the O2 /CO2 mixtures. The experimental results showed good agreement with the results reported in previous works, validating the suitability and reliability of the present experimental method for measuring S L at high pressure. Kinetic modelling was also performed using the GRI-Mech 3.0 and the HP-Mech mechanisms. Both mechanisms predict reasonably well S L and a power factor β that quantifies the dependence of S L on pressure. Thermal-diffusion effects play a major role in the laminar burning velocity decrease due to CO2 dilution at normal and elevated pressures. Kinetic analysis indicated that the reverse of reaction CO + OH = CO2 + H retards the flame propagation in competition with H + O2 = O + OH. Competition of the H consuming reaction H + O2 = O + OH with the two CH3 consuming reactions 2CH3 (+M) = C2 H6 and CH3 + H (+M) = CH4 (+M) leads to a non-monotonic behavior of the overall reaction order for both the N2 - and CO2 -diluted flames.